A rapid parameter configuration method for film hole component in pipe-net calculation. (November 2020) - Li, Jixing; Ning, Tao; Wang, Tian; Hu, Bifu; Xi, Ping; Xu, Jingliang
Film hole component is one of the most important cooling components in pipe-net calculation for blade design. However, owing to a large number of gas film holes, manual parameter configuration for film hole components will affect the efficiency of pipe-net calculation. Extracting parameters from the geometric structure of film holes automatically could significantly shorten the time consumption of pipe-net calculation. In this paper, numeric analysis parameter and group data required by film hole components were summarized and analyzed, based on which a parameter configuration strategy was proposed. Aiming at the extraction of group data, a film hole grouping method was presented. By converting the grouping requirements in fluid-heat analysis into a geometric row pattern recognition problem, it further redefines the geometric row as a linear distribution by a projection method and a parametric mapping method and finally solves the grouping problem by a linear search algorithm. A numeric parameter extraction method was put forward to redefine analysis parameters with geometric properties and identify certain geometry primitives. The proposed algorithm and method are verified with instances. The results illustrate that our method could shorten parameter configuration process of film hole component into several minutes from several hours in manual, with more reliable accuracy.